Bilateral vestibulopathy: a clinical update and proposed diagnostic algorithm - van Stiphout, Lisa; Szmulewicz, David J.; Guinand, Nils; Fornos, Angélica Pérez; Van Rompaey, Vincent; van de Berg, Raymond (Frontiers in Neurology, 2023)
Bilateral vestibulopathy (BVP) is characterized by its heterogeneous and chronic nature with various clinical presentations and multiple etiologies. This current narrative review reflects on the main insights and developments regarding clinical presentation. In addition, it proposes a new diagnostic algorithm, and describes available and potential future therapeutic modalities.